Bacterial pathogenesis : - Salyers, Abigail A. (ASM Press, 2002)
This textbook brings together advances in the understanding of how bacteria cause disease. Research has changed the way scientists view host-bacterium interactions. The interactions involve immunology, cell biology, human and bacterial physiology, molecular biology and genetics. The six introductory chapters provide the scientific background necessary for exploring the bacterial diseases covered in the book. Through studying the bacteria and diseases presented, the book aims to help students gain knowledge of host-parasite interactions, and examine a range of epidemiological and therapeutic problems.